Interactions between Ras and Rap signaling pathways during neurodevelopment in health and disease - Cherra, Salvatore J.; Lamb, Reagan (Frontiers in Molecular Neuroscience, 2024)
The Ras family of small GTPases coordinates tissue development by modulating cell proliferation, cell-cell adhesion, and cellular morphology. Perturbations of any of these key steps alter nervous system development and are associated with neurological disorders. While the underlying causes are not known, genetic mutations in Ras and Rap GTPase signaling pathways have been identified in numerous neurodevelopmental disorders, including autism spectrum, neurofibromatosis, intellectual disability, epilepsy, and schizophrenia. Despite diverse clinical presentations, intersections between these two signaling pathways may provide a better understanding of how deviations in neurodevelopment give rise to neurological disorders. In this review, we focus on presynaptic and postsynaptic functions of Ras and Rap GTPases. We highlight various roles of these small GTPases during synapse formation and plasticity. Based on genomic analyses, we discuss how disease-related mutations in Ras and Rap signaling proteins may underlie human disorders. Finally, we discuss how recent observations have identified molecular interactions between these pathways and how these findings may provide insights into the mechanisms that underlie neurodevelopmental disorders.